2011
DOI: 10.1186/1471-2148-11-83
|View full text |Cite
|
Sign up to set email alerts
|

Plio-Pleistocene sea level and temperature fluctuations in the northwestern Pacific promoted speciation in the globally-distributed flathead mullet Mugil cephalus

Abstract: BackgroundThe study of speciation in the marine realm is challenging because of the apparent absence of physical barriers to dispersal, which are one of the main drivers of genetic diversity. Although phylogeographic studies using mitochondrial DNA (mtDNA) information often reveal significant genetic heterogeneity within marine species, the evolutionary significance of such diversity is difficult to interpret with these markers. In the northwestern (NW) Pacific, several studies have emphasised the potential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
188
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(218 citation statements)
references
References 64 publications
(85 reference statements)
20
188
0
6
Order By: Relevance
“…However, the interrelationship of either stock to any sampling locality, the Kuroshio, or other minor currents was not detected. Similar results have also been observed in other marine fishes in the northwestern Pacific (Chiou and Lee 2004;Liu et al 2007;Han et al 2008a,b;Liu et al 2009;Wu et al 2009;Han et al 2010;Iida et al 2010;Shen et al 2011;Chu et al 2012;Ju et al 2013), in which major ocean current patterns are not good predictors of gene flow. On the other hand, historical factors such as Pleistocene glaciations might account for the genetic pattern of H. oxycephalus.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, the interrelationship of either stock to any sampling locality, the Kuroshio, or other minor currents was not detected. Similar results have also been observed in other marine fishes in the northwestern Pacific (Chiou and Lee 2004;Liu et al 2007;Han et al 2008a,b;Liu et al 2009;Wu et al 2009;Han et al 2010;Iida et al 2010;Shen et al 2011;Chu et al 2012;Ju et al 2013), in which major ocean current patterns are not good predictors of gene flow. On the other hand, historical factors such as Pleistocene glaciations might account for the genetic pattern of H. oxycephalus.…”
Section: Discussionsupporting
confidence: 69%
“…Similar observations were noted for some marine fauna, such as mitten crab, mottled spinefoot, and ice goby in the western Pacific, whose Bayesian skyline plots also indicated that the populations had experienced Pleistocene demographic expansion (Xu et al 2009;Ravago-Gotanco and Juinio-Meñez 2010;Kokita and Nohara 2011). In addition, the TMRCA estimates for all samples of H. oxycephalus indicated that the expansion occurred approximately in the middle Pleistocene period, which is much later than the flathead mullet in this region which occurred in the early Pleistocene period or even in the Pliocene period (Shen et al 2011). The low genetic differentiation among six localities in the northwestern Pacific Ocean, along with the variation mostly found within populations rather than among them (AMOVA , Table 2), implies a high gene flow of H. oxycephalus among populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These changes indicate that the strengthening of the NCCC in the TS weakened in winter because of the increased SSTs. Shen et al (2011) indicated that the regional group of grey mullet belonging to the NCCC might provide a particularly good indicator species for global warming. Our results demonstrate that grey mullet catches exhibited a decreasing trend after 1984, and the fishing ground shifted north following the northward shift of the 20°C isotherm.…”
Section: Effects Of Climate Change On Grey Mullet Catches and Fishingmentioning
confidence: 99%
“…Shen et al (2011) identified three cryptic species of M. cephalus in the northwestern Pacific Ocean and indicated that the distributional range of these species appeared to be governed primarily by three major ocean current systems, the South China Current, North China Coastal Current (NCCC), and Kuroshio Current. Previous studies have reported that the spawning and nursery grounds of the regional group of grey mullet affected by the NCCC are distributed in the coastal waters of the southeastern Taiwan Strait (TS).…”
Section: Introductionmentioning
confidence: 99%